Revisiting Pentecostal spiritualities with reference to African traditional religious practices and Pentecostal theologies of prayer in Ghana - Buertey, Joseph Ignatius Teye (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.